Analysis of the Ministry of Religion's Program in Realizing Religious Moderation in Bantul Regency Society (Peter L. Berger's Social Construction Perspective) - Afriyanto, Dwi; Sri Sumarni; Sembodo Ardi Widodo (PT FORMOSA CENDEKIA GLOBAL, 2024)
Religious moderation is essential to prevent conflict in a diverse society. This study analyzes the program of the Ministry of Religious Affairs in Bantul Regency using Peter L. Berger's social construction theory. Field research with a qualitative approach found that religious moderation is formed through three social dialectic processes: externalization, namely the adaptation of individuals to the social structure of religious moderation through religious texts and figures; objectivation, namely the development of awareness of moderation as a positive action through tradition and institutionalization; and internalization, namely the identification of individuals in the socio-cultural context that forms inclusive and exclusive groups. The program of the Ministry of Religious Affairs in Bantul Regency plays an important role in building a social foundation that supports religious moderation in Bantul.